Prevention and management of radiodermatitis in patients with brachytherapy for gynecologic neoplasms summary of the evidence - Fan, Zhanxin; Liang, Hongxia; Wei, Xin; Cui, Bowen; Wang, Lin (Frontiers in Oncology, 2025)
ObjectiveThis study aims to systematically retrieve, evaluate, and summarize the best evidence regarding the prevention and management of radiation dermatitis in patients undergoing endoluminal radiotherapy for gynecologic neoplasms. The goal is to provide an evidence-based foundation for developing personalized skin management programs.MethodsWe conducted a comprehensive search of domestic and international databases, guideline networks, and the websites of relevant professional associations to identify all evidence related to the prevention and management of radiation dermatitis in patients receiving endoluminal radiotherapy for gynecologic neoplasms. The types of literature include guidelines, evidence summaries, systematic reviews, expert consensus, clinical decision-making, and randomized controlled trials. The search period spanned from database inception to September 2024. In addition, we performed hand-searching of key journals and tracked gray literature (including conference abstracts and unpublishe doi: d reports).ResultsThe review included 14 articles, including 1 clinical decision-making paper, 4 guideline articles, 3 systematic reviews, 3 evidence summary papers, 1 expert consensus document, and 2 randomized controlled trials. We summarized 27 pieces of evidence categorized into 5 themes: assessment and evaluation, health education, general nursing measures, symptom management, and continuity of care.ConclusionsThis study consolidates the most effective evidence for managing radiation dermatitis in patients receiving three-dimensional brachytherapy for gynecologic tumors. The findings can serve as a valuable resource for minimizing skin damage and enhancing patients’ quality of life.Clinical Trial Registrationhttp://ebn.nursing.fudan.edu.cn/home, identifier ES20256976.